ANALISIS KENYAMANAN RUANG TERBUKA HIJAU BERDASARKAN KONDISI FISIK DAN PRESEPSI PENGGUNA (Studi Kasus : Tebet Eco Park ) - Anidar, Arvie Rhasela Nisa; Khuluk, Nazaruddin (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2020)
With green open space, it is one of the most important sections of society's continued survival by observing theirsurroundings. The existence of green open space in urban areas can do good for people especially in terms ofconvenience levels based on the physical conditions of space alignment. A good set of green open Spaces shouldgive a comfortable sense of how to enhance the productivity of the people in them. As for the purpose of this study,identifying the level of comfort and the methods used in this study is a qualitative method that analyzesenvironmental, human aspects, and building aspects. The result of this study was to find out how peopleassessed/perceptions about the physical condition of fixing space on green open space.